Automatic two-digit number processing by people of different age groups and sex - Grabauskaitė, Aida; Daugirdienė, Aušra (Psichologija, 2014)
Currently, there is a growing body of papers on the topic about two-digit (2D) number processing. Separate studies revealed the importance of subjects’ age (e. g., Nuerk, Kaufmann et al., 2004) and sex (Pletzer et al., 2013) in a 2D number representation. The aim of this study was to investigate an automatic 2D number processing in people of different age and sex. 2nd graders (average age 8 years and 5 months), 4th graders (average age 10 years and 5 months), and adults (average age 27 years and 2 months) performed two experimental tasks in which they had to judge the numeric or monetary value of presented stimuli (e. g., which is more, 82 ct or 14 Lt). Results were obtained by totalizing the reaction time and error rate. In statistical analysis, the Wilcoxon criteria were used to distinguish the difference in each participants’ group between blocks of different stimuli. In addition, the results were counted for each participant individually. As in previous studies (e. g., Chan et al., 2011), 2nd graders, 4th graders and adults processed 2D numbers automatically. In this study, 2nd graders processed two-digit numbers in a holistic fashion, while 4th graders and adults used a decomposed parallel processing. The ‘holistic’ 2D number processing in children can be explained as a ‘transition’ stage between decomposed sequential and decomposed parallel. The ‘holistic’ result may derive from approximately equal frequency in using sequential and parallel ways of processing. The data did not support the hypothesis that during adulthood, males process two-digit numbers in a different fashion from females. In this study, both sexes processed 2D numbers in the same way (decomposed parallel). In contrast, Pletzer et al. (2013) found the holistic 2D number processing to prevail in males. In this paper, potential influences on this difference are discussed. First, it could be due to different languages, or it could be due to experiment arrangement. The probability of the same participant using different strategies in response to different (simple or more complex) stimuli is suggested.